PENGARUH LINGKUNGAN KELUARGA TERHADAP MOTIVASI BELAJAR SISWA SETINGKAT SEKOLAH MENENGAH ATAS - Didit Darmawan; Tyas Arjanti (Jurnal Al-Fatih, 2026)
The learning motivation of high school students can be influenced by various factors, including the family environment as the primary educational setting. This study was conducted to analyze the impact of the family environment on the learning motivation of high school students. The study employed a Systematic Literature Review (SLR) approach. The study population included all previous studies discussing the family environment and student learning motivation at the high school level, while the study sample consisted of relevant national scientific articles that met the inclusion criteria. Data collection was conducted by identifying, selecting, and reviewing journal articles that aligned with the study’s focus. The data were analyzed using descriptive-qualitative analysis, which synthesized the research findings to identify patterns of the family environment’s influence on students’ learning motivation. The research results indicate that the family environment generally has a positive and significant effect on students’ learning motivation, as reflected in parental attention, parenting styles, emotional support, a conducive home environment, and the availability of learning facilities. Therefore, the family environment plays a crucial role in fostering students’ learning motivation and needs to be optimized through collaboration between families, schools, and education policymakers.